An empirical study on intention to use hydrogen fuel cell vehicles in India. (29th May 2022) - Kar, Sanjay Kumar; Bansal, Rohit; Harichandan, Sidhartha
Abstract: Demand-side strategies for alternative energy like hydrogen require a thorough understanding of the potential customers' preferences and demand drivers. Multiple studies regarding users' attitudes, intentions, and behavior have been done towards electric vehicles in India, but none so far on hydrogen fuel cell vehicles (HFCVs). Our purpose is to inquire about the key parameters influencing the intention to use HFCVs in India. This empirical research using an online questionnaire was distributed and responses of 483 prospective customers received. To ascertain the users' intentions toward HFCVs, we applied a structural equation modelling approach through Smart-PLS 3.0. We find that perceived benefit, perceived risk, and policy interventions significantly influence the users' intention to adopt HFCV in India. The study suggests that the government must bring together the stakeholders, including automobile manufacturers, hydrogen producers, research institutions, and funding institutions, to address the bottlenecks to fast-track the hydrogen mobility system. Graphical abstract: Image 1 Highlights: We examined consumer intention to use hydrogen fuel cell vehicles (HFCVs). Income (t-value = 2.08) significantly impacts consumer intention to use HFCVs. Perceived benefits (t-value = 7.0) positively influence the intention to use HFCVs. Policy interventions favorably impact the intention to use HFCVs. Consumer awareness towards HFCVs will reduce perceived risk.